Küttner's tumor of the sub-mandibular gland associated with fibrosclerosis and follicular hyperplasia of regional lymph nodes: a case report - Shimamoto Hiroaki; Sakamoto Kei; Kayamori Kou; Omura Ken; Mochizuki Yumi; Yamaguchi Akira (Journal of Medical Case Reports, 2011)
Abstract Introduction Küttner's tumor is characterized through histology by peri-ductal fibrosis, dense lymphocytic infiltration with lymphoid follicles, loss of acini, and occasional marked sclerosis of the salivary gland. On occasion, Küttner's tumor can be difficult to distinguish from malignant neoplasm. Case presentation A 58-year-old Japanese man was referred to our hospital with a three-month history of a painless swollen mass in the right sub-mandibular region. Histological findings revealed both lymphoid follicles with reactive germinal centers and variously sized lymphoid follicle-like nodules without definitive germinal centers or mantle zones. B-cells of similar size and shape occupied the lymphoid follicle-like nodules and stained positive for B-cell lymphoma. These cells were detected in the polyclonal B-cells by flow cytometric analysis and tested negative for CD10. Unusual B-cell proliferation was observed, but as there was no definitive evidence of B-cell lymphoma, the lesion was diagnosed as Küttner's tumor. Conclusion We report on a rare case of Küttner's tumor associated with fibrosclerosis and atypical lymphoid hyperplasia in both the sub-mandibular gland and regional lymph nodes. Although more cases need to be investigated, our findings might be helpful to further studies seeking to clarify the etiology of idiopathic sclerosing lesions arising in the organs and regional lymph nodes.